Nanometer MnP / P / C / CNTs composite material for preparing lithium ion battery and preparation and application of nanometer MnP / P / C / CNTs composite material
The nano MnP/P/C/CNTs composite material addresses the inefficiencies of existing MnP preparation by optimizing milling processes and ratios, resulting in a high-capacity, stable, and energy-efficient lithium-ion battery electrode.
Patent Information
- Application Number
- CN202411456379.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing MnP negative electrode materials for lithium-ion batteries face issues of long preparation time, high energy consumption, low specific capacity, poor red phosphorus agglomeration, and cycle stability, with existing methods producing unstable batteries.
A method involving high-speed and low-speed ball milling of manganese powder, red phosphorus, and expanded graphite, followed by mixing with carbon nanotubes, to form a nano MnP/P/C/CNTs composite material, optimizing the molar ratios and milling conditions to reduce impurities and enhance conductivity.
The method results in a composite material with improved conductivity, reduced impurities, and enhanced cycle stability, suitable for industrial-scale production with low energy consumption and high yield, achieving higher specific capacity and improved lithium storage performance.
Smart Images

Figure CN119230787A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a composite material used in a lithium ion battery, and in particular to a nano MnP / P / C / CNTs composite material used in a lithium ion battery and the preparation and application thereof. Background Art
[0002] As new energy vehicles continue to grow, the requirements for lithium-ion power batteries are getting higher and higher. Currently, lithium-ion batteries with graphite as the mainstream negative electrode can no longer meet the energy needs of new energy vehicles. A higher capacity lithium-ion negative electrode material is needed to meet market needs. MnP is easier to prepare, and its theoretical specific capacity for lithium storage can reach 961mAh·g -1 , while the theoretical specific capacity of graphite is 372 mAh g -1 , making MnP a potential negative electrode material for lithium-ion batteries. Among the methods for preparing battery negative electrode alloy materials, the two mainstream preparation methods are ball milling and tubular furnace sintering. The common preparation method of MnP alloy material is to first mix Mn powder and red phosphorus powder by low-speed ball milling at a rotation speed of 400 rpm for 40 hours, and then put it into a tubular furnace for sintering at a temperature of 980°C for 24 hours. This method not only takes a long time to prepare successfully, but also consumes a lot of energy for sintering, has a low yield, a dangerous preparation process, and many impurities (including Mn3P, Mn2P, and MnO). The prepared lithium-ion battery has poor performance and is only 50mA·g -1 After 50 cycles at a current density of 1.34, the discharge capacity was only maintained at 60 mAh g -1 , the capacity decays too quickly and is extremely unstable. Summary of the invention
[0003] The purpose of the present invention is to provide a nano MnP / P / C / CNTs composite material for preparing lithium ion batteries and its preparation and application, which solves the problems of long preparation time and high energy consumption of existing MnP negative electrode materials, low specific capacity of the prepared battery, poor red phosphorus agglomeration and cycle stability. The method of the present invention not only effectively solves the problem of red phosphorus agglomeration, but also takes a short time and has strong controllability. The prepared MnP / P / C / CNTs composite material has low energy consumption and high yield.
[0004] In order to achieve the above object, the present invention provides a method for preparing a nano MnP / P / C / CNTs composite material for lithium ion batteries, the method comprising:
[0005] (1) Mix manganese powder, red phosphorus and expanded graphite (EG), and perform ball milling at a speed of 1000 r / min to 1200 r / min (high-speed ball milling can well protect the material from the impact of iron filings falling from the iron can during the preparation process, and reduce the impurities generated during the preparation process), to prepare a MnP / P / C composite material; the expanded graphite accounts for 8% to 30% of the total mass of manganese powder, red phosphorus and expanded graphite. A higher EG content is beneficial to the synthesis of the MnP alloy and reduces the formation of iron impurity phase during the ball milling process.
[0006] (2) Mixing the MnP / P / C composite material with carbon nanotubes (CNTs), and ball milling at a speed of 400 r / min to obtain a MnP / P / C / CNTs composite material; the mass ratio of the MnP / P / C composite material to the carbon nanotubes is (80-95): (5-20).
[0007] Preferably, in step (1), the molar ratio of manganese powder to red phosphorus is 1: 2. If the molar ratio of phosphorus powder to manganese powder is too large, impurities such as MnP4 will be ground out, while if it is too small, the reaction will not be sufficient, resulting in excessive manganese content.
[0008] More preferably, the expanded graphite accounts for 20% of the total mass of the manganese powder, red phosphorus and expanded graphite.
[0009] Preferably, in step (1), the ball-to-material ratio of the ball milling is 30:1 and the ball milling time is 8 hours.
[0010] Preferably, in step (2), the mass ratio of the MnP / P / C composite material to the carbon nanotubes is 80:20, 90:10 or 95:5. The higher the CNTs content, the more fully the CNTs and MnP / P / C are mixed during the low-speed ball milling process, which increases the conductivity of the material, releases more energy from the material, and exhibits a greater specific capacity; at the same time, the higher the CNTs content, the less the MnP / P / C content, and the reduction in the MnP alloy content will damage the material's cycle stability in battery performance.
[0011] More preferably, the mass ratio of the MnP / P / C composite material to the carbon nanotubes is 95:5.
[0012] Preferably, in step (2), the ball-to-material ratio of the ball milling is 50:1 and the ball milling time is 20 hours.
[0013] The invention provides a MnP / P / C / CNTs composite material prepared by the preparation method.
[0014] The present invention provides an application of the MnP / P / C / CNTs composite material in preparing a lithium battery.
[0015] The present invention discloses a nano MnP / P / C / CNTs composite material for preparing lithium ion batteries, and its preparation and application, which solves the problems of long preparation time and high energy consumption of the existing MnP negative electrode materials, low specific capacity of the prepared batteries, poor red phosphorus agglomeration and cycle stability, and has the following advantages:
[0016] 1. The present invention uses expanded graphite as a grinding aid, uses high and low speed ball milling methods and a higher EG content, which is beneficial to the synthesis of MnP alloys, reduces the formation of iron impurities during ball milling, and obtains nano MnP / P / C / CNTs composite materials; the nano-sizing of MnP and P shortens the Li + The shuttle pathway of ions entering the active material improves the rate performance of the material; the composite of MnP and P nanoparticles with carbon materials can not only improve the overall conductivity of the material, but also alleviate the volume change of the active material during the charge and discharge process, thereby improving the lithium storage electrochemical performance of the material.
[0017] 2. The preparation method of the present invention has the advantages of simple process, low energy consumption, no pollution, high safety and good sample repeatability, and is suitable for industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a cycle performance diagram of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention.
[0019] Figure 2 This is a SEM image of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention.
[0020] Figure 3 This is the XRD spectrum of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention.
[0021] Figure 4 This is the first charge and discharge curve of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention.
[0022] Figure 5 This is a SEM image of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention.
[0023] Figure 6 This is a cycle performance diagram of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention.
[0024] Figure 7This is a SEM image of the MnP / P / 20wt%C / 5wt%CNTs composite material prepared in Example 3 of the present invention.
[0025] Figure 8 This is a cycle performance diagram of the MnP / P / 20wt%C / 5wt%CNTs composite material prepared in Example 3 of the present invention.
[0026] Fig. 9 This is a flow chart of preparing composite materials for Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The consumables, equipment and their sources used in the following embodiments are as follows:
[0029] Manganese powder (purity ≥ 99.9%, 100 mesh) and red phosphorus powder (purity ≥ 98.5%) were provided by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0030] Expanded graphite (EG) was provided by Qingdao Xinghua Graphite Products Co., Ltd. (purity ≥ 99%, 100 mesh).
[0031] Carbon nanotubes (CNTs) were provided by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. (3-12 microns, purity ≥95%).
[0032] High energy ball mill: QM-3B, vibration mode, Nanjing Nanda Instrument Co., Ltd.
[0033] Planetary ball mill: QM-3SP4, Nanjing Nanda Instrument Co., Ltd.
[0034] Example 1
[0035] A method for preparing a nano-MnP / P / C / CNTs composite material for lithium-ion batteries, such as Fig. 9 As shown, the flow chart of preparing the composite material in Examples 1 to 3 of the present invention comprises:
[0036] (1) Manganese powder, red phosphorus and expanded graphite (the molar ratio of Mn to P is 1:2, and the expanded graphite accounts for 10% of the total mass of manganese powder, red phosphorus and expanded graphite) are mixed and prepared by high-speed ball milling (rotation speed 1200 r / min, ball-to-material ratio of 30:1, ball milling time 8 h) to obtain a MnP / P / 10wt%C composite material.
[0037] (2) The obtained MnP / P / 10wt%C composite material was mixed with carbon nanotubes (MnP / P / 10wt%C accounted for 90% of the total mass, and the mass of carbon nanotubes accounted for 10% of the total mass), and the MnP / P / 10wt%C / 10wt%CNTs composite material was obtained by low-speed ball milling (rotation speed 400r / min, ball-to-material ratio of 50:1, ball milling time of 20h).
[0038] Example 2
[0039] A method for preparing a nano-MnP / P / C / CNTs composite material for lithium-ion batteries is basically the same as that in Example 1, except that:
[0040] In step (2), MnP / P / 10wt%C accounts for 80% of the total mass, and the mass of carbon nanotubes accounts for 20% of the total mass. Through the same operation as in Example 1, a MnP / P / 10wt%C / 20wt%CNTs composite material is obtained.
[0041] Example 3
[0042] A method for preparing a nano-MnP / P / C / CNTs composite material for lithium-ion batteries is basically the same as that in Example 1, except that:
[0043] In step (1), the expanded graphite accounts for 20% of the total mass of manganese powder, red phosphorus and expanded graphite, the rotation speed of the high-speed ball mill is 1150r / min, and the same operation as Example 1 is carried out to prepare a MnP / P / 20wt%C composite material.
[0044] In step (2), MnP / P / 20wt%C accounts for 95% of the total mass, and the mass of carbon nanotubes accounts for 5% of the total mass. Through the same operation as in Example 1, a MnP / P / 20wt%C / 5wt%CNTs composite material is obtained.
[0045] Experimental Example 1 Characterization of Composite Materials
[0046] The composite materials prepared in Examples 1 to 3 were characterized by SEM and XRD, FE-SEM (field emission scanning electron microscope), model: Zeiss Sigma 300, EDS: Bruker Quantax XFlash SDD 6│30 Esprit 2.0. X-ray diffractometer (XRD, Mini Flex 600, Rigaku) used Cu-Kα radiation (4° / min).
[0047] like Figure 2 As shown, the SEM image of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention. Figure 2 It can be seen that the average particle size of the MnP / P / 10wt%C / 10wt%CNTs composite material of Example 1 without obvious agglomeration is 90-100nm, and MnP / P is well combined with CNTs, indicating that the preparation of nanoparticles is successful.
[0048] like Figure 3 As shown in FIG. 1 , the XRD pattern of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention. Figure 3 It can be seen that the MnP / P / 10wt%C / 10wt%CNTs composite material of Example 1 has characteristic diffraction peaks of MnP, indicating that MnP is successfully synthesized.
[0049] like Figure 5 As shown, the SEM image of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention. Figure 5 It can be seen that the average particle size of the MnP / P / 10wt%C / 20wt%CNTs composite material of Example 2 without obvious agglomeration is 90-100nm, and MnP / P is well combined with CNTs, indicating that the preparation of nanoparticles is successful.
[0050] like Figure 7 As shown, the SEM image of the MnP / P / 20wt%C / 5wt%CNTs composite material prepared in Example 3 of the present invention. Figure 7 It can be seen that the MnP / P / 20wt%C / 5wt%CNTs composite material of Example 3 has a good degree of particle refinement, and the average size of small particles without obvious agglomeration is below 100nm.
[0051] Experimental Example 2 Performance of the electrode made from the composite material
[0052] The specific method of electrode assembly is: using deionized water as solvent, mixing the nano MnP / P / C / CNTs composite material (composite material prepared in Examples 1 to 3) with a mass ratio of 8:1:1, a conductive agent (Supli) and a binder sodium carboxymethyl cellulose (CMC), using NMP as solvent to prepare the slurry, coating the prepared slurry on copper foil and placing it in a vacuum drying oven at 80 degrees for 10 hours. Cut the dried current collector into electrode sheets, use the prepared electrode sheets as working electrodes, use metal lithium sheets as reference electrodes, and assemble and use CR2016 button batteries.
[0053] The main components of the electrolyte used in the assembled battery are: 1M LiPF6 as the solute, a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:2 as the solvent, and 10 vol% FEC (fluoroethylene carbonate) as an additive. The electrolyte is provided by Suzhou Duoduo Chemical Technology Co., Ltd., model LB-200.
[0054] The battery test process is as follows: the assembled battery is first left to stand for 24 hours, then tested at room temperature at 100 mA g -1 The first round of discharge was carried out at a current density of 1A·g, and the first round of charge capacity, first round of discharge capacity, charge specific capacity and first coulomb efficiency were tested. The battery was cycled for 5 cycles to form a good and dense SEI film. -1 The discharge capacity after 500 cycles was tested at a current density of . The button battery test instrument used was the Blue Electric Battery Test System CT3001A, provided by Wuhan Blue Point Electronics Co., Ltd. (specification model 5V10mA8C).
[0055] like Figure 1 As shown in FIG. 1 , the cycle performance diagram of the MnP / P / 10wt%C / 10wt%CNTs composite material prepared in Example 1 of the present invention. Figure 1 It can be seen that the MnP / P / 10wt%C / 10wt%CNTs electrode of Example 1 has a -1 The first-round discharge and charge specific capacities at the current density were 723.6 mA h g -1 and 579.2 mA h g -1 , the first coulombic efficiency is 80.04%; at 1A·g -1 At a current density of 1.5 %, the discharge capacity remains at 400 mAh g after 500 cycles. -1 above.
[0056] like Figure 4 As shown in FIG. 1 , the first charge-discharge curve of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention. Figure 4 It can be seen that the MnP / P / 10wt%C / 20wt%CNTs electrode of Example 2 has a voltage range of 0.01 to 3.0V and a -1 The first round charging capacity at the current density is 637.6 mAh g -1 , the first round discharge capacity is 972.8mAh·g -1 , the first coulombic efficiency is 68.72%.
[0057] like Figure 6As shown in FIG. 1 , the cycle performance diagram of the MnP / P / 10wt%C / 20wt%CNTs composite material prepared in Example 2 of the present invention. Figure 6 It can be seen that the MnP / P / 10wt%C / 20wt%CNTs electrode of Example 2 has a -1 At a current density of 1.547 W, the discharge capacity remained at 450 mAh g after 500 cycles. -1 above.
[0058] like Figure 8 As shown in FIG. 3 , the cycle performance diagram of the MnP / P / 20wt%C / 5wt%CNTs composite material prepared in Example 3 of the present invention. Figure 8 It can be seen that the MnP / P / 20wt%C / 5wt%CNTs electrode of Example 3 has a -1 At a current density of 1.547 W, the discharge capacity remained at 570 mAh g after 500 cycles. -1 above.
[0059] Comprehensive analysis of the above Figures 1 to 8 It can be seen that, compared with Example 1 and Example 2, Example 2 has a higher content of CNTs. During the low-speed ball milling process, CNTs and MnP / P / C are mixed more fully, increasing the conductivity of the material, so the material releases more energy and exhibits a larger specific capacity; the excessive content of CNTs in Example 2 means that the content of MnP / P / C is less. By comparing the experimental data of Example 1 and Example 2, it can be seen that the reduction of the MnP alloy content will damage the cycle stability of the material in battery performance. Example 3 uses 1150rpm and 20% EG. The use of EG as a grinding aid can well protect the material in high-speed ball milling to reduce the impact of iron filings falling in the iron can during the preparation process and reduce the impurities generated during the preparation process.
[0060] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing a nano-MnP / P / C / CNTs composite material for lithium-ion batteries, characterized in that: The method includes: (1) mixing manganese powder, red phosphorus and expanded graphite, and ball milling at a speed of 1000 r / min to 1200 r / min to prepare a MnP / P / C composite material; The expanded graphite accounts for 8% to 30% of the total mass of manganese powder, red phosphorus and expanded graphite; (2) mixing the MnP / P / C composite material with carbon nanotubes, and ball milling at a speed of 400 r / min to prepare the MnP / P / C composite material; The mass ratio of the MnP / P / C composite material to the carbon nanotubes is (80-95): (5-20).
2. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of the manganese powder to the red phosphorus is 1:
2.
3. The preparation method according to claim 2, characterized in that: The expanded graphite accounts for 20% of the total mass of the manganese powder, red phosphorus and expanded graphite.
4. The preparation method according to claim 1, characterized in that: In step (1), the ball-to-material ratio of the ball milling is 30:1 and the ball milling time is 8 hours.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the MnP / P / C composite material to the carbon nanotubes is 80:20, 90:10 or 95:
5.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the MnP / P / C composite material to the carbon nanotubes is 95:
5.
7. The preparation method according to claim 1, characterized in that: In step (2), the ball-to-material ratio of the ball milling is 50:1 and the ball milling time is 20 hours.
8. A MnP / P / C / CNTs composite material obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the MnP / P / C / CNTs composite material as claimed in claim 8 in the preparation of lithium batteries.
